A kind of ionic liquid-containing lubricant composition and the method for realizing superlubricity

CN118028042BActive Publication Date: 2026-10-16JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311820766.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2026-10-16
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

然而,单纯的类离子液体作为润滑剂难以实现超润滑

Benefits of technology

[0017] This invention uses a certain amount of carbon quantum dots as competitive ligands to interact with ionic liquids that are multi-hydroxyl hydrogen bond donors. By adjusting the cluster size distribution width/span, the friction coefficient during relative motion of the friction pair can be effectively reduced, achieving super-lubrication after a brief run-in process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118028042B_ABST
    Figure CN118028042B_ABST
Patent Text Reader

Abstract

The application discloses a kind of containing ionic liquid-like lubricant composition, comprising: polyhydroxy hydrogen bond donor ionic liquid and carbon quantum dots;Carbon quantum dots account for 0.6-0.9% of the mass of lubricant composition;The number of hydroxyl contained in the polyhydroxy hydrogen bond donor is 3.It also discloses a kind of method for realizing superlubricity, comprising: the lubricant composition is coated on the surface of friction pair, and realizes superlubricity after running-in;Friction condition includes: load 2-4N, temperature is 20-25 DEG C, linear velocity is 60-200mm / s, and friction time is greater than or equal to 10s.The application uses polyhydroxy hydrogen bond donor ionic liquid as base lubricating fluid, and uses carbon quantum dots as competitive ligand, and carbon quantum dots can effectively regulate the size distribution width / span of cluster in lubricating fluid, greatly reduce the friction coefficient when friction pair relative movement, realize superlubricity (friction coefficient <0.01) after short running-in process of friction pair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lubricating materials, and particularly relates to a lubricant composition containing ionic liquids and a method for achieving superlubricity. Background Technology

[0002] Friction is ubiquitous and constant. In mechanical systems, lubrication failure due to friction and wear between components is very common, severely impacting the efficiency and lifespan of machinery and causing significant energy loss. Statistics show that friction consumes one-third of the world's energy, approximately 80% of mechanical parts fail due to wear, and over 50% of serious accidents involving mechanical equipment are caused by lubrication failure. Therefore, minimizing friction and wear has become a major focus of attention.

[0003] Superlubrication is a lubrication state where the coefficient of friction μ reaches the order of 0.001 or lower. It is currently an important means to solve the aforementioned friction and wear problems and meet the development needs of modern precision machinery and advanced technologies. Traditional lubricants generally have a coefficient of friction higher than 0.1, making it difficult to achieve superlubrication. Ionic liquids have advantages such as being green, inexpensive, easy to synthesize, biocompatible, and having tunable physicochemical properties, making them a potential candidate for novel green lubricants. However, pure ionic liquids alone cannot achieve superlubrication as lubricants.

[0004] Therefore, it is of practical significance to provide a green, super-lubricating lubricant based on ionic liquids. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a lubricant composition containing an ionic liquid, in which carbon quantum dots, as a competing ligand for the polyhydroxy hydrogen bond donor ionic liquid, can achieve stable superlubricity.

[0006] The specific solution of this invention is as follows:

[0007] One objective of this invention is to provide a lubricant composition containing an ionic liquid, comprising: a polyhydroxy hydrogen bond donor ionic liquid and carbon quantum dots; the carbon quantum dots account for 0.6-0.9% of the mass of the lubricant composition; and the polyhydroxy hydrogen bond donor contains three hydroxyl groups.

[0008] In the lubricant composition of the present invention, a polyhydroxy hydrogen bond donor ionic liquid is used as the base lubricant, and carbon quantum dots are used as competing ligands. Carbon quantum dots can effectively regulate the distribution width / span of cluster size in the lubricant, thereby improving the performance of the base lubricant, greatly reducing the coefficient of friction when the friction pair moves relative to each other, achieving super-lubrication (coefficient of friction < 0.01) after a short running-in process of the friction pair, and increasing the load-bearing capacity.

[0009] Preferably, in the polyhydroxy hydrogen bond donor ionic liquid, the polyhydroxy hydrogen bond donor is glycerol.

[0010] Preferably, in the polyhydroxy hydrogen bond donor ionic liquid, the hydrogen bond acceptor is selected from any one of choline chloride, zinc chloride, fluorinated choline, brominated choline, triphenylphosphine, tetrabutylphosphine bromide, and triphenylphosphine bromide.

[0011] Preferably, in the polyhydroxy hydrogen bond donor ionic liquid, the molar ratio of hydrogen bond acceptor to polyhydroxy hydrogen bond donor is 1:2-8.

[0012] The carbon quantum dots described in this invention are not specifically limited, and can be commercially available or prepared using conventional methods. Methods for preparing carbon quantum dots include, but are not limited to, the condensation reaction of a strong base with an aldehyde; wherein the strong base includes, but is not limited to, sodium hydroxide, and the aldehyde includes, but is not limited to, acetaldehyde. The carbon quantum dots described in this invention have surfaces rich in various oxygen-containing functional groups such as carboxyl and hydroxyl groups.

[0013] The preparation method of ionic liquids is not specifically limited, including but not limited to the conventional one-step synthesis method: the hydrogen bond donor and the hydrogen bond acceptor are mixed evenly in a certain molar ratio, and then heated and stirred to form a homogeneous and stable liquid.

[0014] Preferably, the lubricant combination is prepared by mixing a polyhydroxy hydrogen bond donor ionic liquid and carbon quantum dots in a certain proportion and then dispersing them ultrasonically.

[0015] The second objective of this invention is to provide a method for achieving super-lubrication, comprising: coating the lubricant composition described in any one of the above claims onto the surface of a friction pair, and achieving super-lubrication after break-in; the friction conditions include: a load of 2-4 N, a temperature of 20-25 °C, a linear velocity of 60-200 mm / s, and a friction time of ≥10 s; the friction pair is selected from any one of silicon nitride / silicon dioxide, silicon nitride / sapphire, and silicon nitride / steel.

[0016] The beneficial effects of this invention are:

[0017] This invention uses a certain amount of carbon quantum dots as competitive ligands to interact with ionic liquids that are multi-hydroxyl hydrogen bond donors. By adjusting the cluster size distribution width / span, the friction coefficient during relative motion of the friction pair can be effectively reduced, achieving super-lubrication after a brief run-in process. Attached Figure Description

[0018] Figure 1 The curve showing the change in the coefficient of friction of the lubricant composition described in Example 1 over time;

[0019] Figure 2 The curve showing the change in the coefficient of friction of the lubricant composition described in Example 2 over time;

[0020] Figure 3 The curve showing the change in the coefficient of friction of the lubricant composition described in Example 3 over time;

[0021] Figure 4 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 1 over time;

[0022] Figure 5 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 2 over time;

[0023] Figure 6 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 3 over time;

[0024] Figure 7 The curve showing the change of the friction coefficient of the lubricant described in Comparative Example 4 over time;

[0025] Figure 8 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 5 over time;

[0026] Figure 9 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 6 over time;

[0027] Figure 10 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 7 over time;

[0028] Figure 11 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 8 over time;

[0029] Figure 12 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 9 over time;

[0030] Figure 13 The curve showing the change in the coefficient of friction of the lubricant described in Comparative Example 10 over time;

[0031] Figure 14 The NMR spectra of the lubricants described in Examples 1-2 and Comparative Examples 4-5 are shown below.

[0032] Figure 15 The cluster size distribution width / span of the lubricants described in Examples 1-2 and Comparative Examples 4-5;

[0033] Figure 16 To determine the particle size distribution and span diagram of liquid clusters in Examples 2-3 and Comparative Examples 9-10;

[0034] Figure 17 To establish a relationship between span and friction coefficient for the data in Examples 1-3 and Comparative Examples 4-5 and 9-10. Detailed Implementation

[0035] The technical solution of the present invention will be described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0036] Tribological experiments were conducted using an MPX-3G ball-disc friction and wear testing machine for the lubricants used in the following examples and comparative examples. The experimental conditions were: load 3N, linear velocity 80mm / s, temperature 20-25℃, and the friction materials were silicon nitride balls with a diameter of 5mm and a quartz glass disk, with a friction time of 1 hour.

[0037] Example 1

[0038] A lubricant composition containing an ionic liquid comprises, by mass percentage: 0.6% carbon quantum dots, with the balance being a choline chloride-glycerol ionic liquid; wherein the molar ratio of choline chloride to glycerol in the choline chloride-glycerol ionic liquid is 1:8.

[0039] The frictional properties of the lubricant composition described in this embodiment were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 1 As shown, super lubrication is achieved during and after a short run.

[0040] Example 2

[0041] A lubricant composition containing an ionic liquid comprises, by mass percentage: 0.9% carbon quantum dots, with the balance being a choline chloride-glycerol ionic liquid; wherein the molar ratio of choline chloride to glycerol in the choline chloride-glycerol ionic liquid is 1:8.

[0042] The frictional properties of the lubricant composition described in this embodiment were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 2 As shown, super lubrication is achieved during and after a short run.

[0043] In the lubricant system described in this invention, the maximum addition amount of carbon quantum dots is 0.9%, and they are difficult to dissolve if the amount exceeds this.

[0044] Example 3

[0045] A lubricant composition containing an ionic liquid comprises, by mass percentage: 0.9% carbon quantum dots, with the balance being a zinc chloride-glycerol ionic liquid; wherein the molar ratio of zinc chloride to glycerol in the zinc chloride-glycerol ionic liquid is 1:8.

[0046] The frictional properties of the lubricant composition described in this embodiment were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 3 As shown.

[0047] Depend on Figure 2 and Figure 3The comparison shows that replacing the hydrogen bond acceptor with zinc chloride results in a slightly worse lubrication effect, but stable superlubrication can still be achieved.

[0048] Comparative Example 1

[0049] A lubricant comprising only an ionic liquid, said ionic liquid comprising, in a molar ratio of: choline chloride: glycerol = 1:2.

[0050] The frictional properties of the lubricant described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 4 As shown.

[0051] Comparative Example 2

[0052] A lubricant comprising only an ionic liquid, said ionic liquid comprising, in a molar ratio of: choline chloride: glycerol = 1:4.

[0053] The frictional properties of the lubricant described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 5 As shown.

[0054] Comparative Example 3

[0055] A lubricant comprising only an ionic liquid, said ionic liquid comprising, in a molar ratio of: choline chloride: glycerol = 1:6.

[0056] The frictional properties of the lubricant described in this comparative example were tested, and the coefficient of friction changing over time is shown in the curve below. Figure 6 As shown.

[0057] Comparative Example 4

[0058] A lubricant comprising only an ionic liquid, said ionic liquid comprising, in a molar ratio of: choline chloride: glycerol = 1:8.

[0059] The frictional properties of the lubricant described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 7 As shown.

[0060] As can be seen from the comparison of friction performance in Comparative Examples 1-4 above, different molar ratios of choline chloride and glycerol have different lubricating effects. Among them, the coefficient of friction is the smallest when the ratio of choline chloride to glycerol is 1:8, but super lubrication is not achieved.

[0061] Comparative Example 5

[0062] A lubricant composition comprising, by mass percentage: 0.3% carbon quantum dots, with the balance being a choline chloride-glycerol ionic liquid; wherein the molar ratio of choline chloride to glycerol in the choline chloride-glycerol ionic liquid is 1:8.

[0063] The frictional properties of the lubricant composition described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 8 As shown.

[0064] It can be seen that superlubricity cannot be achieved when the amount of carbon quantum dots added is 0.3%.

[0065] Comparative Example 6

[0066] A lubricant composition comprising, by mass percentage: 0.9% carbon quantum dots, with the balance being a choline chloride-erythritol ionic liquid; wherein the molar ratio of choline chloride to erythritol in the choline chloride-erythritol ionic liquid is 1:2 (maximum ratio).

[0067] The frictional properties of the lubricant composition described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 9 As shown in the figure, replacing the polyhydroxy hydrogen bond donor with erythritol resulted in a poorer lubrication effect, failing to achieve superlubricity.

[0068] Comparative Example 7

[0069] A lubricant composition comprising, by mass percentage: 0.9% carbon quantum dots, with the balance being a choline chloride-xylitol ionic liquid; wherein the molar ratio of choline chloride to xylitol in the choline chloride-xylitol ionic liquid is 1:2 (maximum ratio).

[0070] The frictional properties of the lubricant composition described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 10 As shown in the figure, replacing the polyhydroxy hydrogen bond donor with xylitol resulted in a decrease in lubrication, failing to achieve superlubrication.

[0071] Comparative Example 8

[0072] A lubricant composition comprising, by mass percentage: 0.9% carbon quantum dots, with the balance being a choline chloride-sorbitol ionic liquid; wherein the molar ratio of choline chloride to sorbitol in the choline chloride-sorbitol ionic liquid is 1:2 (maximum ratio).

[0073] The frictional properties of the lubricant composition described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 11 As shown in the figure, replacing the polyhydroxy hydrogen bond donor with sorbitol resulted in a decrease in lubrication, failing to achieve superlubrication.

[0074] Comparative Example 9

[0075] A lubricant composition comprising, by mass percentage: 0.9% carbon quantum dots, with the balance being a choline chloride-ethylene glycol ionic liquid; wherein the molar ratio of choline chloride to ethylene glycol in the choline chloride-ethylene glycol ionic liquid is 1:8.

[0076] The frictional properties of the lubricant composition described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 12 As shown in the figure, replacing the polyhydroxy hydrogen bond donor with ethylene glycol resulted in a decrease in lubrication, failing to achieve superlubrication.

[0077] The comparison of the frictional properties of Comparative Examples 6-9 and Example 2 shows that when the number of hydroxyl groups in the polyhydroxy hydrogen bond donor is ≥3, the friction coefficient increases with the increase of the number of hydroxyl groups; when the number of hydroxyl groups is ≤3, the friction coefficient decreases with the increase of the number of hydroxyl groups. Therefore, the lubricant composition exhibits optimal frictional properties when the number of hydroxyl groups in the polyhydroxy hydrogen bond donor is 3.

[0078] Comparative Example 10

[0079] A lubricant composition comprising, by mass percentage: 0.9% carbon quantum dots, with the balance being a zinc chloride-ethylene glycol ionic liquid; wherein the molar ratio of zinc chloride to ethylene glycol in the zinc chloride-ethylene glycol ionic liquid is 1:8.

[0080] The frictional properties of the lubricant composition described in this comparative example were tested, and the coefficient of friction changing over time is shown in the figure below. Figure 13 As shown.

[0081] It can be seen that in the zinc chloride-based hydrogen bond acceptor lubricant system, the lubrication effect deteriorated after replacing the polyhydroxy hydrogen bond donor with ethylene glycol, and superlubricity was not achieved, indicating that glycerol plays a very important role in the lubrication process.

[0082] The following are other test conditions and results.

[0083] 1. The lubricants of Examples 1-2 (carbon quantum dot addition amount of 0.6% and 0.9%) and Comparative Examples 4-5 (carbon quantum dot addition amount of 0% and 0.3%) were tested to investigate the effect of carbon quantum dot addition amount on the lubricant, as detailed below:

[0084] (1) The lubricants of Examples 1-2 and Comparative Examples 4-5 were subjected to nuclear magnetic resonance spectroscopy, and the results are as follows: Figure 14 As shown, the position of the hydroxyl groups in glycerol changes with the addition of carbon quantum dots, indicating that the carbon quantum dots alter the chemical environment of glycerol. This demonstrates that the carbon quantum dots do indeed play a competitive ligand role in the polyhydroxy hydrogen bond donor ionic liquid described in this invention.

[0085] (2) The lubricants of Examples 1-2 and Comparative Examples 4-5 were diluted with ultrapure water to approximately 20% of their opacity, and then uniformly dispersed. The particle size distribution of the carbon quantum dots and ionic liquid clusters was then determined using a laser diffraction particle size analyzer (Mastersizer 2000), and the distribution was then calculated according to the formula...

[0086]

[0087] The median diameter is the particle size representing 50% of the cumulative particle size distribution, used to calculate the span. The results are as follows: Figure 15 As shown.

[0088] It can be seen that carbon quantum dots act as competitive ligands in choline chloride-glycerol ionic liquids, regulating the width / span of cluster size distribution in the lubricating fluid.

[0089] 2. The particle size distribution of the liquid clusters in Examples 2-3 and Comparative Examples 9-10 was measured respectively, and the span was calculated according to the formula. The results are as follows. Figure 16 As shown.

[0090] 3. Establish the relationship between the friction coefficient and span for the data in Examples 1-3 and Comparative Examples 4-5 and 9-10, such as... Figure 17 As shown.

[0091] It can be seen that the cluster size distribution width is approximately positively correlated with the span, while the span is approximately negatively correlated with the friction coefficient.

[0092] 4. The wear scar diameters of Examples 1-3 and Comparative Examples 4-5 and 9-10 were measured, and the contact pressure was calculated, as shown in Table 1 below.

[0093] Table 1 shows the wear scar diameter, contact pressure, span, and average coefficient of friction.

[0094]

[0095] It can be seen that the cluster span is approximately positively correlated with the contact pressure and approximately inversely correlated with the friction coefficient. When the size distribution width / span of the clusters in the lubricant increases, the load-bearing capacity of the system can be improved and the friction coefficient can be reduced. As in Examples 1 and 2, when the span increases from 3.5 to 4.0, the final contact pressure of the system increases from 493 MPa to 596 MPa, and the friction coefficient decreases from 0.0078 to 0.0024, and stable macroscopic superlubricity can be achieved.

[0096] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A lubricant composition containing an ionic liquid, characterized in that, include: Polyhydroxyl hydrogen bond donor ionic liquids and carbon quantum dots; carbon quantum dots constitute 0.6-0.9% of the lubricant composition by mass; The number of hydroxyl groups in the polyhydroxy hydrogen bond donor is 3; in the polyhydroxy hydrogen bond donor ionic liquid, the polyhydroxy hydrogen bond donor is glycerol; the hydrogen bond acceptor is selected from any one of choline chloride, zinc chloride, fluorinated choline, brominated choline, triphenylphosphine, tetrabutylphosphine bromide, and triphenylphosphine bromide.

2. The lubricant composition containing an ionic liquid according to claim 1, characterized in that, In polyhydroxy hydrogen bond donor ionic liquids, the molar ratio of hydrogen bond acceptor to polyhydroxy hydrogen bond donor is 1:2-8.

3. The lubricant composition containing an ionic liquid according to claim 1 or 2, characterized in that, The preparation method is as follows: a polyhydroxy hydrogen bond donor ionic liquid and carbon quantum dots are mixed in a certain proportion and then ultrasonically dispersed.

4. A method for achieving superlubricity, characterized in that, include: The lubricant composition according to any one of claims 1-3 is applied to the surface of the friction pair, and super lubrication is achieved after running-in; the friction conditions include: load of 2-4N, temperature of 20-25℃, linear velocity of 60-200mm / s, and friction time ≥10s. The friction pair is selected from any one of silicon nitride / silicon dioxide, silicon nitride / sapphire, or silicon nitride / steel.

Citation Information

Patent Citations

  • Additive for lubricating liquid and ionic liquid-like lubricating liquid

    CN115895765A

  • Environment-friendly water-based cutting fluid with excellent lubricating and anti-rust performance and preparation method of environment-friendly water-based cutting fluid

    CN116376629A